HER/ErbB receptors in normal epithelium and in malignant transformation - Szacikowska, Ewa; Kozłowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2000)
In the paper the most important features of the receptors from the HER/ErbB family and their ligands are presented. The HER receptors transmit signals to DNA dependent on the pool of available growth factors or the degree of their exhaustion, and determine thus the quality of the signal that sets down a given number of cell divisions after which the cells undergo ultimate differentiation. Then it is shown how expression change of these receptors leading to increase of their number due to oncogenic activation of the genes encoding these receptors is followed by a change of their function. They react no more to external regulation of cell growth but, being constitutionally active, they send continuous false mitogenic signals to the cell nucleus, provoking continuous divisions of such cells. The particular role is discussed of the HER2/HER3 heterodimer which is one of the most aggressive oncoproteins. In the paper the three-point axis is also presented, determined by the action of three oncoproteins which are the basis for disturbing of normal cell growth leading to neoplastic transformation and progression of malignant phenotype in neoplastic epithelial cells. On the ground of the results of most recent basic and clinical studies and newest confirmed hypotheses, cyclo-oxygenase 2, HER2/HER3 heterodimer, and auto/intracrine expression of heregulins (HRG) have been determined as the cooperating and mutually regulating oncoproteins, causing the most malignant tumours – epithelial neoplasms with HER2 gene amplification and/or overexpression.